Agriculture packaging design in China: a study of form and meaning towards the construction of national identity - Chen, Tao (2025)
In the context of deepening globalization, national identity has increasingly become a significant field of interdisciplinary research. It is widely recognized as a key factor influencing not only a country’s cultural cohesion and social stability but also its ability to project a strong and consistent image on the international stage.. This study takes Chinese agricultural packaging design as the starting point to explore its form and significance in the construction of national identity. Specifically, it is guided by three interrelated research questions: What are the historical foundations and conceptual evolution of Chinese national identity? In what ways do specific visual and material design elements in agricultural packaging embody national symbols and cultural narratives? And how does packaging design contribute to shaping and promoting the image of Chinese agriculture within domestic and global contexts? Methodologically, this research employs a mixed qualitative approach, combining comprehensive literature review, content analysis, visual semiotics, and case studies. The empirical component includes an in-depth analysis of 100 agricultural packaging samples across categories such as rice, tea, and meat, alongside qualitative interviews with 20 participants from diverse professional and social backgrounds. The findings reveal that agricultural packaging design in China transcends its functional role as a marketing tool, serving also as a cultural and symbolic medium. It reinforces narratives of heritage, tradition, and modernity, supporting the broader project of cultural continuity and nation branding. This study contributes to the academic discourse on design and national identity by highlighting how packaging can operate as a vehicle for cultural expression and identity construction. It also offers practical insights for designers, policymakers, and stakeholders involved in cultural and agricultural branding strategies.